Transformaciones en el sistema alimentario y cambios de dieta en España durante el siglo XX - Alicia Langreo; Luis Germán (Historia Agraria)
This article reflects on how changes in the Spanish food system have been instrumental in changing the availability and consumption of foods in the twentieth century. We designed several stages in the study and examined several sectors that have experienced major changes. The first stage refers to the first decades of the twentieth century, prior to the Spanish Civil War, and immediately after the war; the second spans from the early fifties to the beginning of the seventies; and the third go from then until the end of the century. Throughout the first three quarters of the century there were major innovations in agriculture and industry, in contrast to a very poor traditional retail distribution system. In the fourth sections of the article, major changes that occurred during the last quarter of the century in food distribution and growing control over the food chain are analyzed in relation to the rapid expansion and increasing concentration of large-scale retail distribution. These changes affected traditional buying habits and consumption, shifting food expenditures towards higher-quality, healthier, processed and personalized goods; as well as increasing food consumption outside the home.